Early Distal Radius Remodeling after Radius Dome Osteotomy in Madelung's Deformity - Rus, Robert; Scheider, Philipp; Farr, Sebastian (Journal of Wrist Surgery, 2023)
Background Distal radius realignment procedures such as the dome osteotomy have been shown to reliably correct the geometry of this three-dimensional deformity. However, it has not been clarified whether the correction is durable over time. We thus reviewed a prospective Madelung's database and evaluated all patients who received a radius dome osteotomy to see whether there was any loss of correction over time.Patients and Methods A total of 16 patients with 19 operated wrists were included. Mean age at surgery was 14 years; the most recent radiograph that was considered for analysis was obtained at a mean of 20 months after the index surgery. Three established radiographic deformity parameters (ulnar tilt, lunate subsidence, palmar carpal displacement) were repetitively measured by an independent observer over the course of the postoperative follow-up and compared using the analysis of variance statistics.Results A mild but nonsignificant worsening of deformity parameters was observed in six patients (32%). Overall, ulnar tilt improved from 50 to 40 degrees after surgery and was 43 degrees at latest follow-up. The values for lunate subsidence were −5.5, 0, and −1.6 mm, respectively. Palmar carpal displacement did not recur after correction (21, 17, and 16 mm, respectively).Conclusions Frontal plane parameters remodeled to a certain degree, although not in a statistically significant manner, soon after corrective osteotomies in Madelung's deformity. Although mild surgical overcorrection may be warranted in younger patients, it remains unclear if a concomitant distal radial epiphysiodesis would generally be beneficial.Level of Evidence Level IV
Keywords: Madelung's deformity; radius deformity; radius dome osteotomy; ulnar tilt; lunate subsidence; palmar carpal displacement